2022
DOI: 10.1039/d1ob02358f
|View full text |Cite
|
Sign up to set email alerts
|

A strong hydride donating, acid stable and reusable 1,4-dihydropyridine for selective aldimine and aldehyde reductions

Abstract: A 1,4-dihydropyridine derivative, lacking carbonyl groups and containing bulky aryl substituents, was synthesized and found to have a high hydride donating ability, acid resistance and reusability. Thermodynamic parameters for electron...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Synthesis of ( E )‐2,6‐dibromo‐4‐(phenyldiazenyl)pyridine , B : 2,6‐Dibromopyridin‐4‐amine was prepared in three steps starting from 2,6‐dibromopyridine according to a previously reported procedure [21] . The ( E )‐2,6‐dibromo‐4‐(phenyldiazenyl)pyridine, B was then prepared from 2,6‐dibromo‐4‐aminopyridine by a procedure similar to the synthesis of A [5a] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Synthesis of ( E )‐2,6‐dibromo‐4‐(phenyldiazenyl)pyridine , B : 2,6‐Dibromopyridin‐4‐amine was prepared in three steps starting from 2,6‐dibromopyridine according to a previously reported procedure [21] . The ( E )‐2,6‐dibromo‐4‐(phenyldiazenyl)pyridine, B was then prepared from 2,6‐dibromo‐4‐aminopyridine by a procedure similar to the synthesis of A [5a] .…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of (E)-2,6-dibromo-4-(phenyldiazenyl)pyridine, B: 2,6-Dibromopyridin-4-amine was prepared in three steps starting from 2,6-dibromopyridine according to a previously reported procedure. [21] The (E)-2,6-dibromo-4-(phenyldiazenyl)pyridine, B was then prepared from 2,6-dibromo-4-aminopyridine by a procedure similar to the synthesis of A. [5a] The crude product was then purified by column chromatography over 100-200 mesh silica gel using 1 : 15 mixture of ethyl acetate:hexane to give an orange-coloured solid.…”
Section: Synthesis Of (E)-4-(phenyldiazenyl)-2-(1h-pyrazol-1-yl)pyridinementioning
confidence: 99%
See 2 more Smart Citations
“…Although the aforementioned bioinspired synthetic design is intriguing, there are three challenging issues that must be addressed to successfully implement this strategy. First, how can regioselective electrophilic halogenation be achieved at the C3=C14 double bond in 16 , rather than the unexpected electrophilic halogenation occurring at the electron-rich indole moiety? Additionally, it has been extensively demonstrated that 1,4-dihydropyridine compounds bearing an indole unit, such as 16 , readily aromatize to form the corresponding pyridinium salts . Furthermore, to the best of our knowledge, there is only one literature report on the reaction of this specific compound with an electrophile (using HBr), and no previous examples exist for its reaction with other electrophilic reagents.…”
mentioning
confidence: 99%